Towards seamless navigation - Peltola, Pekka; Moore, Terry (Springer International Publishing, 2017)
Seamless navigation using one single mobile device would ease navigation. This goal demands detection of context. That is the environment (outdoor, indoor, car, etc.) and behaviour (walk, run, climb, etc.) of the location and user. Each positioning technology (inertial, radio frequency, sound, etc.) has its inherent characteristics. If correctly designed, the navigation system uses multiple sensors and combines the best characteristics of the available sensors in an optimal way. Battery consumption and accuracy of the system meets the needs for all environments. The user would not be aware of how the device works so well all the time—a seamless navigation device. This chapter provides a review of the available sensors and methods that can be used to complement GNSS, in scenarios where GNSS is not enough for seamless navigation.